Digital content on mobile devices (a music perspective). - Ong, Khuan Wee. (2008)
This project focuses on the value proposition of digital music content in the context of a wireless mobile world. Three forces, namely technology, law and human behavior are defined which will impact the music and wireless industry in the near future. The focus of music is chosen because the uptake of digital music media is leading the technology field as compared to other media forms.